ANALISIS PENDAPATAN USAHA TERNAK ITIK PETELUR DI KECAMATAN BANYUBIRU KABUPATEN SEMARANG - A. S. Noviyanto; W Roessali; M Handayani (Universitas Wahid Hasyim, 2016)
The present study of revenue laying duck in District Banyubiru aims to determine the amount of revenue duck in District Banyubiru, the value of the profitability and the factors that affect revenue in the District Banyubiru duck. The material used is to create the framework that contains the main review in limits - limits about of laying ducks, revenues and profits. The research was conducted in several stages, which includes determining the location, sampling, data collection and analysis of research data and preparing reports. The data obtained is then collected then analyzed descriptive and quantitative. Enterprises duck in the District of Semarang District Banyubiru feasible to develop this is evidenced from the average profitability of 31.94% is bigger than the interest rate on bank deposits 1 month (0.14%) significantly. Simultaneously the cost of feed effect onrevenue. Partially that affect the variable cost of feed, the amount of production,and duckday, while the cost of drugs has no effect on income. Keywords: Ducks laying; revenue; expenses; profitability